"Goodbye to the Gangstas": The NBA Dress Code, Ray Emery, and the Policing of Blackness in Basketball and Hockey. (February 2014) - Lorenz, Stacy L.; Murray, Rod
This article assesses cultural representations of Blackness in the National Basketball Association (NBA) and the National Hockey League (NHL) in relation to contemporary forms of racism in North American society. In particular, this case study examines media narratives surrounding the adoption of the NBA dress code and the behavior of NHL goaltender Ray Emery during the 2005 to 2006 basketball and hockey seasons. Despite significant differences in the racial composition of the two leagues, the NBA and the NHL made similar efforts to discipline, police, and contain the young Black males under their control. Racialized constructions of Black athletes as menacing, criminal, and dangerously different were prominent in media coverage of both sports. An exploration of these sporting controversies offers a transnational and comparative framework for understanding racial discourses in the United States and Canada today.